2022
DOI: 10.37934/mjcsm.8.1.1123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Printing Orientation and Layer Thickness on Microstructure and Mechanical Properties of PLA Parts

Abstract: Due to the layer-by-layer printing process, additively manufactured objects frequently display directional dependencies in their structure. It affects the material properties of the fabricated parts concerning various process parameters of the machine. This paper presents the effect of layer thickness and printing orientation on the mechanical properties and microstructure of polylactic acid (PLA)3D printed parts fabricated by Fused Deposition Modeling (FDM). Computer-aided design models of a tensile and compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our findings suggest that molds are susceptible to heat, which can increase the size of the structure. Specifically, we found that PLA structures had the highest increment in size compared to PETG and SLA as research by Hamid et al, [27]. Similarly, the PDMS microchannels fabricated using PLA molds showed the highest increment in size compared to those made with SLA and PETG.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings suggest that molds are susceptible to heat, which can increase the size of the structure. Specifically, we found that PLA structures had the highest increment in size compared to PETG and SLA as research by Hamid et al, [27]. Similarly, the PDMS microchannels fabricated using PLA molds showed the highest increment in size compared to those made with SLA and PETG.…”
Section: Discussionsupporting
confidence: 77%
“…At the end of the observation, it showed that the SLA mold gave the most accurate size compared to PLA and PETG. SLA also showed the lowest increment, which is very important in molding applications because any difference between the product and the 3D printed mold would affect the application which also reviewed in the research by Hamid et al, [27].…”
Section: The Effect Of Heated Microchannel Mold On the Pdms Microflui...mentioning
confidence: 85%
“…It is essential for the estimation of the mechanical strength of the structure. It also depends on the parameters of the 3D printing, such as printing orientation and layer thickness [22]. Therefore, we can find out the failure part of the project before the product is fabricated.…”
Section: Stress and Strain Analysis Using Solidwork 2013mentioning
confidence: 99%
“…Thus, based on the results in this study, it could be reasonably inferred that increasing metal loadings would yield higher hardness values in parts subjected to sintering process provided that the void/defect content is <20%. Nevertheless, despite the promising hardness results, further mechanical testing through tensile tests is necessary to discuss the mechanical properties more comprehensively in the future [34][35][36].…”
Section: Hardness Measurementsmentioning
confidence: 99%